Innovative Business Development-A Global Perspective 25th International Economic Conference of Sibiu (IECS 2018) (Springer Proceedings in Business and Economics,, 2018)
This proceedings volume presents the latest trends in innovative business development theory and practice from a global, interdisciplinary perspective. Featuring selected contributions from the 25th International Economic Conference Sibiu (IECS 2018) held in Sibiu, Romania, it explores various topics in the areas of economics, business, finance and accounting, including tourism, marketing and Islamic banking and finance. Written by researchers from different regions and sectors around the world, it offers significant insights into the emerging shifts that characterize the fields of innovative economics and global development, innovative business practices, as well as innovative finance and banking, and provides organizations, managers and policy makers with new reliable solutions and opportunities for innovative development and growth within and between organizations around the globe.